Information Technology Awareness And Its Relationship With Self – Actualization and Performing Some Rope Skills In Rhythmic Gymnastics - Layth, Khlood (Journal of Physical Education, 2012)
In chapter one the researcher tackled information technology awareness and its relation with self awareness and its effect on personality and behavior. The researcher studied their effect on rope skills in rhythmic gymnastics. The problem of the research lays in identifying the role of information technology and its relationship with self – actualization and performing some rope skills in Rhythmic Gymnastics. The researcher stated the aims of the study as well as the hypotheses. In chapter two tackled information technology and self – actualization in details. Chapter three discusses the method used in the research as well as the skill tests and measurements used in information technology and self – actualization. The subjects were 40 students. The results were discussed and analyzed in tables in chapter four. In the final chapter, the researcher concluded that information technology awareness and its relation with self – actualization led to a great improvement in the level of skill performance. The researcher recommended the necessity of paying attention to information technology and enhancing self – actualization in all sport skills because they are a very important factor for development .